FDTD Analysis of a Probe-Fed Dielectric Resonator Antenna in Rectangular Waveguide - Zhang, Yizhe; Kishk, Ahmed A.; Yakovlev, Alexander B. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
Dielectric resonator antennas (DRA) are characterized for operation in a guided-wave environment with the ultimate goal of their use in modeling of waveguide-based DRA amplifier arrays for spatial power combining. Performance of a single probe-fed DRA element in rectangular waveguide is analyzed by varying design parameters of the DRA and the feeding probe to optimize the structure for the scattering characteristics (port matching and coupling). The effect of hard walls on the DRA behavior is also studied. The numerical analysis of waveguide-based DRA elements is based on the Finite-Difference Time-Domain (FDTD) method and a coaxial probe is modeled by a thin wire approximation implemented in the FDTD algorithm. The numerical results are compared with those generated by using commercial software and exhibit a very good agreement.